Beton - Concrete : best of Detail. (Munchen : Detail, 2016)
Multi-layered, multi-faceted and malleable like no other building material – concrete offers enormous potential for the future. Depending on its composition, the uses for concrete range from simple furnishings to impressive interior designs, from fascinating façades to wide-spanning support structures. Love it or hate it, concrete is part of the building culture and – whether filigree, sculptural or massive – it's here to stay thanks to the wealth of construction and design possibilities it offers our urbanised environment. Best of DETAIL Concrete brings together highlights from DETAIL magazine from the past few years about this expressive building material. In addition to interesting professional insights and articles, the publication provides a comprehensive section of case studies – from train stations to family homes to churches – that offer inspiration for individual design work.